(untitled) (Malaysian Journal of Civil Engineering, 2019)
Situational leadership is defined as a style of leadership in which a leader manages to adapt his/her style in order to suit the situation. This situation refers to the circumstances among the leader’s employee which could enhance the success of the related project/work. The study is aimed to determine the suitability between the type of the employee and the situational leadership style of the project manager on a construction company. The circumstances of the employee are represented by their commitment and competence maturity level. The suitability result could give an insight to the project manager to enhance the success of their project. This study utilises a descriptive statistical analysis through a questionnaire survey and interview to a construction company in Indonesia. This company is selected because it is one of the biggest construction company in Indonesia. This research observed four high rise building projects which are constructed by this company in 2017 in Bandung, Indonesia. The result summary of the four projects shows a suitability between the type of employee (D3) and the project’s manager situational leadership style (S3). In accordance with the situational leadership theory, this suitability could produce a great situation between project manager and his/her employee, enhancing the accomplishment of the project. The company should keep this suitability, if such a shifting happens among the team, a re-identification is recommended. This could help project manager to understand his/her new employee, so he/she could adapt to the new situation and transform his/her leadership style to fit the new type of employee. This could enhance the overall performance of the company.